Protective effects of Rosa roxburghii Tratt. extract against UVB-induced inflammaging through inhibiting the IL-17 pathway - Shuhong Zhang; Yueyue Chen; Liping Qu (Scientific Reports)
Abstract Chronic inflammation is a critical mechanism contributing to the aging process; however, research specifically addressing chronic inflammation in skin biology remains limited. This study investigates the protective mechanism of Rosa roxburghii Tratt. (RRT) extract against UVB-induced inflammaging. RRT extract effectively reduces the secretion of IL-6, IL-1α, TNF-α, and PGE2 in keratinocytes. Additionally, it attenuates UVB-induced IL-17 pathway activation by downregulating IL-17RA, c-Fos, and c-Jun protein levels, as well as the gene expression of IL-17RA, TRAF6, HSP90, and IKKγ. Co-culturing human foreskin fibroblasts (HFF) with inflammatory factors secreted by UVB-exposed keratinocytes reveals that these factors significantly reduce mitochondrial membrane potential and mitochondrial reactive oxygen species (ROS), thereby promoting aging in HFF. The anti-inflammaging effects of RRT extract are achieved through the reduction of β-galactosidase activity, targeting of the TGF-β1-Smad2/3 signaling pathway, upregulation of COL1A1 expression, and reduction of senescence-associated secretory phenotype secretion. This study provides a novel perspective and robust scientific foundation for exploring mechanisms of skin aging and potential therapeutic interventions.